IMPLEMENTATION OF WEB-BASED E-LEARNING MODEL TO BUILD THE FOURTH-GRADE STUDENTS’ LEARNING MOTIVATION ON THE IPA THEMATIC LEARNING IN MADRASAH IBTIDAIYAH - Lusi Oktavia; Irfan Irfan; Rusdy Iskandar; Afifah Rizki; Nurul Huda (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Research indicates that learning motivation is crucial to determine a successful learning process for students. In fact, the reality in the research field, students' motivation for Natural Science learning subjects in elementary schools is still lacking. The researcher will subsequently apply or examine the learning models. The research is conducted to explain whether the implementation of web-based e-learning in thematic learning, especially Natural Science learning subjects, can build students' learning motivation or not. The research location was conducted at Madrasah Ibtidaiyah Plus Nur Rahma in Bengkulu. The time of conducting the research is the even semester in the academic year 2021/2022. The method used is a qualitative approach. Data collection is direct interview and documentation techniques. The research results imply that implementing an e-learning model can increase students' learning motivation. The implication of the research is that teachers or thematic learning for Natural Science learning subjects in elementary schools are recommended to utilize this web-based e-learning learning model.Â